Evaluation of Roundabout Performance in the Sudirman Central Business District (SCBD), Jakarta - Siti Raudhatul Fadilah; Fairuz Muhammad Ananta (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2026)
The Sudirman Central Business District (SCBD) in Jakarta is characterized by high-intensity, mixed-use activities that generate substantial traffic demand throughout the day. This study evaluates the operational performance of the Lot 13 roundabout, one of the district’s critical internal nodes, using a combination of field observations, analytical assessment, and a microscopic simulation model developed in PTV Vissim. The simulation approach was selected because similar roundabout studies in Indonesia remain largely dominated by analytical capacity assessment, with fewer calibrated microsimulation-based evaluations in dense CBD environments characterized by mixed traffic and high roadside friction.. Traffic data were collected at 15-minute intervals during peak periods and used to construct a detailed behavioural model calibrated to local driving characteristics, including short headways and aggressive merging behaviour typical of mixed traffic in Indonesia. The results reveal severe oversaturation on the Sudirman–Grand Lucky and Sudirman–BEI legs, where maximum queue lengths exceed 550 meters, delays surpassing 70–100 seconds per vehicle, and circulating speeds reduced to 12–18 km/hour, placing the roundabout at Level of Service F. Geometric constraints, high roadside friction, and unbalanced approach volumes further degrade operational capacity, demonstrating that the current unsignalized configuration is insufficient to accommodate prevailing demand. The findings suggest that adaptive signal control or metering signals may represent promising options for further operational performance by creating controlled entry gaps and reducing conflict intensity. The study provides a site-specific operational diagnosis of the Lot 13 roundabout and highlights the combined role of unbalanced approach demand, limited effective entry capacity, and roadside friction in shaping queue formation, delay, and flow breakdown in a dense CBD setting. Recommendations for future research include the evaluation of multi-scenario design alternatives and the assessment of broader network-level impacts to support long-term mobility planning in SCBD.